The deepest wounds : a labor and environmental history of sugar in Northeast Brazil - Rogers, Thomas D., 1974- (University of North Carolina Press, 2010)
This study traces social and environmental changes over four centuries in Pernambuco, Brazil's key north-eastern sugar-growing state. Focusing particularly on the period from the end of slavery in 1888 to the late twentieth century, when human impact on the environment reached critical new levels, the author confronts the day-to-day world of farming - the complex, fraught, and occasionally poetic business of making sugarcane grow.